SUPPLY CHAIN MANAGEMENT UNTUK UMKM: KUNCI EFISIENSI & DAYA SAING - Hasibuan, Rizki Prakasa; Jamal, Siti Aisyah; Herman, Herman; Afrija, Fritalia; Khotimah, Nabila Husnul (JURNAL REKAYASA SISTEM INDUSTRI, 2025)
The participation of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia’s industrial supply chains remains critically low, accounting for only 6.3% of the total 65.5 million MSMEs. This condition highlights the urgency of implementing strategic measures to enhance their integration into the national industrial ecosystem. This study aims to examine the existing conditions of MSME supply chains and to develop an efficient supply chain management (SCM) model aligned with their operational capacities. The research was conducted in two phases: (1) an assessment of current supply chain practices through a survey of 25 MSMEs in the food and handicraft sectors in Batam City, and (2) the design and simulation of an SCM model involving three partner MSMEs. The findings reveal that most MSMEs lack stable supplier networks, do not employ systematic production scheduling, and have yet to adopt information technology in their operations. To address these challenges, a Hybrid Collaborative SCM (HCSM) model comprising five core components was developed. Simulation results indicate significant improvements in delivery lead times, transportation costs, production cycle times, and a reduction in stock-out frequencies, thereby demonstrating the model’s potential to enhance MSME supply chain performance